Collaborative learning in recycling practice: Pride of the Malay heritage / Nor Sabrina Zahari ... [et al.] - Zahari, Nor Sabrina; Zahari, Mohd Fahmi; Zahari, Mohamad Faiz; Shaar, Arbaayah (2023)
Recycling awareness among young educated generation especially school’s children is critical as the flag-bearer of the world in the future. From the ideas of educators to promote awareness of recycling programs and sustainability, then results in one of the initiatives established in recycling practices that is Periwinkle Landscape Innovation in SK Aur Gading, Kuala Lipis Pahang. SK Aur Gading is one of the rural area schools and parsley populated area in Pahang. Periwinkle is the symbolic of flowers to give hope and benefit to cancer patients. Varieties of innovation in teaching and learning is not only focus on applying new technology but the way on how to diversify the available resources or facilities to bring something good in the future. This initiative will move school to an environment friendly domain and more importantly the campaign fosters students' leadership by enabling students to be more creative by involving this innovative programme that also can be apply in teaching and learning process.